2020
DOI: 10.3390/su12145846
|View full text |Cite
|
Sign up to set email alerts
|

Information Sources and Constraints to Climate Change Adaptation amongst Smallholder Farmers in Amathole District Municipality, Eastern Cape Province, South Africa

Abstract: With current global climate change conditions, the urgency to provide agricultural knowledge on adaptation has risen. The dearth of climate change information is one amongst many agricultural production challenges faced by the majority of rural farming communities. This study aimed to identify smallholder farmers’ sources of climate change information and constraints to their coping and adaptation. Descriptive statistical tools, mean scores and the ‘problem confrontation index’ (PCI) were used to assess and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 98 publications
(137 reference statements)
4
30
0
Order By: Relevance
“…Few farmers received climate information from the government (less than 2%) and non-governmental organizations (NGOs) (less than 4%). A recent study found that radio and TV are potential sources of climate information for farmers in Eastern Cape Province, South Africa [36]. According to the climate change, agriculture, and food security (CCAFS) program, due to climate-informed advisory services and other innovations, climate information reaches about 7 million farmers through rural radio in Senegal.…”
Section: Sources Of Farmers' Climate Informationmentioning
confidence: 99%
“…Few farmers received climate information from the government (less than 2%) and non-governmental organizations (NGOs) (less than 4%). A recent study found that radio and TV are potential sources of climate information for farmers in Eastern Cape Province, South Africa [36]. According to the climate change, agriculture, and food security (CCAFS) program, due to climate-informed advisory services and other innovations, climate information reaches about 7 million farmers through rural radio in Senegal.…”
Section: Sources Of Farmers' Climate Informationmentioning
confidence: 99%
“…Creating the knowledge base that underpins its access and use, however, faces two challenges: Climate solutions have a shelf life, and they are very context specific. Therefore, the way knowledge regarding climate change and variability is produced, transferred, and exchanged is extremely relevant to securing equitable and inclusive scaling-up pathways (Popoola et al, 2020;Roncoli et al, 2010).…”
Section: Transformative Knowledge Managementmentioning
confidence: 99%
“…Farmers identified the most critical adaptation constraint being a lack of access to extension and other advisory services that help them mediate and assimilate the relevant information. The lack of information on climate change coupled with a knowledge gap in coping strategies were also identified as critical constraints in Nigeria, Ghana and Pakistan (Popoola et al 2020).…”
Section: Partnerships For Knowledge Management and Capacity Buildingmentioning
confidence: 99%